Diversitas Kultural dan Pengelolaan Konflik Dalam Sebuah Organisasi Bisnis Multinasional - MC Ninik Sri Rejeki (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2011)
The theoritical analysis is inspired by the labor riot occurred in Drydocks World Graha Shipyards Company in Batam April 22, 2010. This case has reminded us to consider the importance of diversity management for business organization. Such organization has a reality of cultural diversity in its employees and usually it is a multinational company. Such company has grown and expanded in accordance with the development of the global economic order. The reality of cultural diversity actually can be positive forces to sustain the dynamics of the organization, but if not properly managed it can make the negative impact of disadvantageous communication climate. It can enrich the communication climate practices of racism and discrimination. The goal of diversity management is to maximize the positive forces of cultural diversity and to minimize its negative impacts. Management of diversity is itself a way of managing an organization that requires the multicultural paradigm. Inter-group conflict management is an integral part of the management of diversity. At the group level, it is necessary to understand the factors of inter-group conflict. When the conflict as the adverse effect of cultural diversity occurs, that is needed is a constructive management. Parties who have a burden of adaptation should be accommodative to other parties. Accommodation is conducted in the way of viewing the conflict, attitudes, and management style. It is also needs to be developed a communication climate that may reduce the prejudices which is the source of the practices of racism and discrimination.